Oaks and beeches in Spain. Genetic resources conservation - Goikoetxea, P. G.; Agundez, D. (Forest Systems, 2000)
Spain is an active member in EUFORGEN Social Broadleaves Network since 1999. This network includes Beech and European white oaks. Quercus spp includes a complex of species intimately related geneticaly and ecologicaly. It therefore reveals the Iberic Peninsula, together with F. sylvatica, as an interesting emplacement with a high genetic potential sharing the species nemoral and mediterranean climate. In this paper a revision of the conservation state of the forest genetic resources of oaks and beech is presented. The problematic of these species is also studied as well as an evaluation of the works already done towards this area in order to be able to define a conservation program of the genetic resources. Actually we have available information about geographic variation of the species across the delimitation of regions of provenance and regions of identification and use. The filogenetic relationship studied through chloroplast DNA reveals 2 European lineages for Beech and various lineages from inside and outside the Iberian Peninsula for Oaks, indicating furthermore a strong relationship within it. The structure of the genetic diversity is partially known for Beech showing a clear geographic trend. There are several provenance tests for Beech, an evaluation of which is essential to learn about the behavior of our genetic material and to be able to make recommendations for the use of the species. When Oaks are considered the situation is more precarious and studies aiming the knowledge of genetic variation must be reinforced.